Covid-19 and industrial restructuring: What future for transnational value chains? - Giacomo Cucignatto; Matteo Gaddi; Nadia Garbellini (European Trade Union Institute (ETUI), 2022)
The economic and health crisis triggered by the Covid-19 pandemic leaves the European Union facing the steepest decline in production and employment since the Second World War, on top of economic fundamentals that are already fragile as a result of the disastrous effects of the double fall associated with the great financial crisis and the sovereign debt crisis. This paper shows that, in the absence of an industrial policy aimed at changing the structure of the EU's productive system, the transformation of global demand currently taking place will mostly benefit the Asian economy with China increasingly assuming industrial supremacy to the detriment of the US. The EU, in its turn, is going to accumulate growing gaps in terms of productive capacity within different supply chains - with the partial exception of Germany. In order to achieve a transition that is not only environmental but also social, a European industrial policy is needed for the creation and public management of at least four industrial sectors, broadly defined: semiconductors - whose production is triggered by final demand for an extremely broad range of commodities, in particular TLC devices and personal computers; hydrogen electrolysers, solar panels and wind turbines; TLC equipment such as personal computers, smartphones, tablets - and in general connectivity devices; and public transport equipment.
Keywords: 330; Internationaler Wettbewerb; Strukturwandel; Halbleiterindustrie; EU-Staaten